Storage Temperature Impacts on Anthocyanins Degradation, Color Changes and Haze Development in Juice of “Merlot” and “Ruby” Grapes (Vitis vinifera) - Muche, Bizuayehu M.; Speers, R. Alex; Rupasinghe, H. P. Vasantha (Frontiers in Nutrition, 2018)
This study evaluated the degradation kinetics of selected anthocyanins and the change in polymeric color, browning index, and haze development of grape juices from ‘Merlot’ and ‘Ruby’ grape cultivars stored at 5, 25, and 35oC for up to 360 days. Five major anthocyanins namely malvidin-3-O-glucoside (M3G), delphinidin-3-O-glucoside (D3G), petunidin-3-O-glucoside (Pt3G), peonidin-3-O-glucoside (Pn3G), and cyanidin-3-O-glucoside (C3G) were identified. Juice from ‘Merlot’ had significantly higher (p < 0.05) content of all individual anthocyanins as compared to ‘Ruby’. During the long-term storage, total and individual anthocyanins from both cultivars degraded following first-order reaction kinetics at the rate strongly dependent on temperature. At the end of the storage, noticeably higher loss of anthocyanins (95-99.9%) was observed at 25 and 35oC as compared to storage at 5oC [50-60% (‘Merlot’); 74-81% (‘Ruby’)]. Considerably lower rate of decay was observed at 5oC (k = 0.01-0.04) as compared to 25 (k = 0.04-0.14) and 35oC (k = 0.05-0.14) storage temperatures. The most temperature sensitive anthocyanin compounds were C3G (Ea = 66.5 kJ/mol) and D3G (Ea = 63.3 kJ/mol). At higher storage temperatures, significant (p < 0.05) and strong negative correlations were observed between anthocyanin concentrations and the levels of haze, polymeric and brown color development during storage. Storing grape juice, at lower temperature conditions could reduce the sustained loss of biologically active anthocyanins as well as the development of haze and brown color.